Quando as mulheres negras se movimentam: identidade e trajetórias profissionais de mulheres negras no mundo branco - Silva, Andréa Franco Lima e (2023)
Occupying spaces has been one of the purposes of social movements that demands political leadership and social recognition. Black women still struggle to make this change in various professional fields such as politics, entertainment, journalism, literature, among others; also, in occupying management and leadership positions in public entitie s, or disputing the private market, spaces that are usually denied to these women. This research seeks to understand how Black women who occupy certain professional positions experience this social place, considering their educational and career trajectory , how their “integration” or the lack of it takes place in white spaces, and if they mainly experience the senses of belonging or non belonging to these places. Their trajectories reveal power relations and forms of reproduction of sexist, racist and c lassism structures, as well as forms of confrontation, social transformation and resistance. There is an intersection of oppression that will make the look of the black woman a unique perspective on the place she occupies and on the relationships of belong ing and exclusion.